MEDIATOR TEACHER: CHALLENGES IN THE SCHOOL INCLUSION OF CHILDREN WITH AUTISTIC SPECTRUM DISORDER - Maria Bochi Silva, Élida; Paula Bochi, Ana; Rocha Lopes, Juliana; Pereira Gusmão, Jacqueline; Teixeira Lima, Larissa; da Silva Dias, Edcler; Cristina de Oliveira Amorim Pedro, Viviane; de Souza Oliveira, Renata (Revista Gênero e Interdisciplinaridade, 2024)
The proposal of this study was to review the literature related to the role of the mediator teacher in the school inclusion of children with autistic spectrum disorder. In general, the review of the literature performed enabled the elucidation of the main challenges of teaching practice in the mediation role of students with autistic spectrum disorder.